Diagnosticiranje arterijske hipertenzije pri otroku in mladostniku - Marčun-Varda, Nataša (Slovenska pediatrija, 2012)
In the article the diagnostic evaluation of children and adolescents with hypertension is briefly reviewed. These children have to be actively sought, as they often have no symptoms. When persistently elevated blood pressure has been confirmed, diagnostic evaluation should be performed, with investigations focused on a search for the secondary cause of hypertension, on assessment of associated comorbidities, target organ damage, additional cardiovascular risk factors, and on estimation of the total cardiovascular risk of the individual patient. All speps in the diagnostic procedure are important when the decision is made to initiate appropriate treatment. The selection of necessary investigations to find the cause of hypertension should take into account the age of the child, level of blood pressure, clinical signs and symptoms and family history. A careful history, physical examination and focused investigations will identify the cause in most cases, without the need for extensive diagnostic evaluation.
Keywords: Adolescent; arterijska hipertenzija; Child; Diagnosis; Diagnostika; Hipertenzija; Hypertension; Mladostnik; mladostniki; otroci; Otrok